2003
DOI: 10.1590/s1516-89132003000100015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biological variables and capture period on the proximate composition and fatty acid composition of the dorsal muscle tissue of Hypophthalmus edentatus (Spix, 1829)

Abstract: This study analyzed the chemical composition of the dorsal muscle tissue of Hypophthalmus edentatus, in particular, fatty acids of the lipidic fraction, and its relationship with the biological variables and the capture period. The average values for moisture, ash, protein and total lipids were 63.15, 1.11, 14.27 and 17.24%, respectively. In the lipidic fraction, 35 fatty acids were identified, the most abundant being: 16:0, 18:1omega9, 18:0, 16:1omega7, 18:3omega3, DHA and EPA. The totals of respectively satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 23 publications
4
16
0
7
Order By: Relevance
“…Values of the overall means of various parameters of composition (water, fat, protein, organic and ash contents), analyzed in the whole wet body weight of wild Mystus bleekeri have values that are very similar to those reported for the whole body composition of various species, whether farmed or wild Pongchawee et al, 1995;Oliveira, 2003;Ball, 2007;Turan, 2007;Naeem et al, 2010a;. Predictive equations using regression analysis were developed in this study, as many workers have found high degree of accuracy by using it.…”
Section: Discussionsupporting
confidence: 75%
“…Values of the overall means of various parameters of composition (water, fat, protein, organic and ash contents), analyzed in the whole wet body weight of wild Mystus bleekeri have values that are very similar to those reported for the whole body composition of various species, whether farmed or wild Pongchawee et al, 1995;Oliveira, 2003;Ball, 2007;Turan, 2007;Naeem et al, 2010a;. Predictive equations using regression analysis were developed in this study, as many workers have found high degree of accuracy by using it.…”
Section: Discussionsupporting
confidence: 75%
“…The variation in chemical composition of Tilapia species was affected by seasonal variation. In different environmental conditions, the values of body composition of the same fish may differ in relation to difference in water quality, feeding conditions, sex, state of maturity (Javaid et al, 1992) and capture period of the fish (Oliveira et al, 2003). An increase in protein, fat and decrease in water content showed in spring and winter and vise versa in summer and autumn.…”
Section: Proximate Composition Analysismentioning
confidence: 99%
“…En muchas especies, como algunas de agua dulce de la Argentina, los contenidos de grasa y proteína están correlacionados entre sí [18] e igualmente relacionados con el tamaño de los peces en general [8,11,17]. Estas relaciones no se observaron en las especies aquí estudiadas, aunque el pequeño rango de tamaño de los ejemplares analizados pudo influir en el resultado de la relación con el tamaño.…”
Section: Resultados Y Discusiónunclassified